Dividend payouts: majority control and rent extraction - Besim, Seniha; Adaoglu, Cahit (Journal of Business Economics and Management, 2018)
In Eurasia, Turkey has a “crony” capitalist system with majority control and business groups (BGs) in the hands of a few families. These business groups are often organised around a holding company. We analyse the dividend payouts of family controlled Borsa Istanbul companies, which are affiliated to holding and non-holding BGs. We investigate and quantify the effects of several control-enhancing mechanisms (CEMs) on dividend payouts. We use precise quantitative proxies for CEMs to measure the divergence between control and ownership rights. Supporting the rent extraction hypothesis, holding business group companies have lower dividend payouts as the divergence between control and ownership rights widens and the pyramid wedge increases. However, controlling foreign-family coalitions in holding business group companies curb the rent extraction problem by having a positive effect on the dividend payouts. Overall, for family controlled holding BG companies, the effects of company-specific financial control variables on dividend payouts are stronger than the effects of CEMs. For family controlled non-holding BG companies, there is no empirical support for either the rent extraction or the reputation building hypotheses. The company-specific financial control variables are the main determinants of dividend payouts for family controlled non-holding BG companies.